Reflow soldering process for Sn3.5Ag solder on ENIG using rapid thermal processing system - Nor Adhila Muhammad,; Badariah Bais,; Ibrahim Ahmad, (Universiti Kebangsaan Malaysia, 2014)
A study on reflow soldering process for Sn3.5Ag solder on ENIG substrate was performed using the rapid thermal processing (RTP) system. The reflow soldering process by RTP system can be successful, but it is sensitive to some typical defects. A poor RTP system design can lead to significant temperature differences where non-uniform heating or cooling may result in material failure due to increase in thermal stresses or serious damage. From this study, it was found that at a peak temperature (Tpeak) of 251°C, the reflowed solder was observed to be smooth joint appearance over the solder pad and formed a regular joint shape of the solder due to the efficient reflow profile and sufficient heating input during the reflow process. The Ni3Sn4 intermetallic compounds were found to be continuous, thus resulting in a good metallurgical bonding between Sn3.5Ag solder and ENIG substrate. Meanwhile, an uneven reflowed solder and defect mechanism was detected at Tpeak of 246 and 260°C. This is due to the inadequate reflow profile and insufficient heating input during the reflow soldering process in the RTP system. Visual micrographs of reflowed solder and cross-sectional micrograph and elemental analysis were presented in this paper for better understanding of the defect mechanism in order to optimize the reflow soldering process using RTP system. The reflow soldering process can be performed better with appropriate reflow profile in the RTP system in order to achieve a good solder joint of Sn3.5Ag solder and ENIG substrate.